2007
DOI: 10.1038/sj.npp.1301488
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immune Challenge Induces Sex-Dependent Depressive-Like Behavior and Cytokine Expression in the Brain

Abstract: The association between activation of the immune system and mood disorders has been reported by several studies. However, the mechanisms by which the immune system affects mood are only partially understood. In the present study, we detected depressive-like behavior in a rat animal model which involves the induction of inflammation in the nasal cavities by intranasal (i.n.) instillation of bacterial lipopolysaccharides (LPS). Female rats showed depressive-like behavior as evidenced by the forced swim test afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 98 publications
10
72
0
5
Order By: Relevance
“…In any case, our results, which are consistent with our animal data (35,52), indicate that anxiety symptoms are correlated with upper respiratory inflammatory symptoms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In any case, our results, which are consistent with our animal data (35,52), indicate that anxiety symptoms are correlated with upper respiratory inflammatory symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that the relationship between allergic disease and depression is a major phenomenon, and seemingly more robust than the one between allergic disease and measures of anxiety. However, our animal model data point towards a more consistent association between anxiety-like behaviors rather than depressive-like behaviors and with sensitization and exposure to tree pollen allergen (35,52). To further analyze this triangular relationship between allergy, depression, and anxiety, we will continue our research with primary anxiety disorders and primary non-comorbid mood disorders.…”
Section: Discussionmentioning
confidence: 88%
“…In this regard, it should be highlighted that while there is abundant information about gender differences in suicide risk factors and suicidal behavior, to our knowledge, postmortem studies have not reported major neurochemical or gene expression differences between the brain of suicides women and men. The observed sex-differences in cytokine expression in the present study may be of relevance because sex-differences in the immune and cytokine response of the brain have been reported in experimental animal models (46)(47)(48). Therefore, cytokines may further our understanding of neurochemical sex-differences in the brain that may be related to sex-differences in behavior.…”
Section: Discussionmentioning
confidence: 78%
“…This problem could be addressed by the use of standard and validated FST procedures already described for male rodents (Slattery and Cryan, 2012). Regarding the oestrous cycle, most studies show that the phase of the oestrous cycle does not influence basal female FST behavioural performance in a significant way (Alonso et al, 1991;Bravo and Maswood, 2006;Jans et al, 2007;Tonelli et al, 2008; Andrade et al, 2010;Craft et al, 2010; Allen et al, 2012;Kokras et al, 2012;Flores-Serrano et al, 2013). However, the oestrous cycle could play a role in antidepressant response, but the studies using standard antidepressants in intact female rats during different phases of the cycle are limited (Marvan et al, 1996;Barros and Ferigolo, 1998;Contreras et al, 1998;Consoli et al, 2005; Allen et al, 2012;Dalla et al, 2012;Flores-Serrano et al, 2013).…”
Section: Sex Differences In Animal Models Of Depressionmentioning
confidence: 99%